The effect of leverage and profitability on carbon emissions disclosure in Indonesia’s financial sector - Simon, Simon; Andini, Ivo Putri Viddy; Nabila, Prita Rizki; Marsintauli, Frihardina (Privietlab, 2025)
This study aims to examine the effect of leverage and profitability on carbon emissions disclosure among financial sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. A quantitative approach was employed using secondary data obtained through purposive sampling methods. Of the 105 companies, only 64 met the criteria. The data were analyzed using multiple linear regression with SPSS 30. The findings revealed that both leverage and profitability have a significant influence on carbon emissions disclosure. Companies with higher leverage and greater profitability tend to disclose more information related to carbon emissions. This behavior is likely driven by the perceived strategic benefits of environmental transparency, particularly in enhancing investor appeal and reinforcing competitive advantage. These results highlight the role of financial performance indicators in promoting environmental accountability in Indonesia’s financial sector.